2020
DOI: 10.1016/j.heliyon.2020.e04731
|View full text |Cite
|
Sign up to set email alerts
|

Exploring substance use disorders and relapse in Mauritian male addicts

Abstract: Background Substance Use Disorder (SUD) places a heavy burden on societal and health systems given its association with high mortality and morbidity rates worldwide, including Mauritius. Illicit substances act as a positive reinforcement and stimulate addiction through its pleasure-seeking attributes. Aim This study focused on identifying the risk factors leading to SUD among Mauritian male addicts as well as examining the potency of those factors in SUD development. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 93 publications
2
8
0
4
Order By: Relevance
“…Although findings revealed that tramadol abuse is more associated with abstinence and multiple drug abuse is in association with relapse, a regression study revealed that the type of drug abused and drug polyconsumption had no significant relationship with relapse, implying that recurrence was unrelated to the number of substances used. This outcome was consistent with Ramo et al 's research [56], the Mauritian study [50], and Chalana et al 's study [27]. These results are inconsistent with the study done in Icyzere, Rowanda, finding that patients with polysubstance use were more likely to relapse than those who only used one substance [53].…”
Section: Regarding Predictors Of Relapse Among Both Groups (Relapsed ...supporting
confidence: 58%
See 2 more Smart Citations
“…Although findings revealed that tramadol abuse is more associated with abstinence and multiple drug abuse is in association with relapse, a regression study revealed that the type of drug abused and drug polyconsumption had no significant relationship with relapse, implying that recurrence was unrelated to the number of substances used. This outcome was consistent with Ramo et al 's research [56], the Mauritian study [50], and Chalana et al 's study [27]. These results are inconsistent with the study done in Icyzere, Rowanda, finding that patients with polysubstance use were more likely to relapse than those who only used one substance [53].…”
Section: Regarding Predictors Of Relapse Among Both Groups (Relapsed ...supporting
confidence: 58%
“…Individuals in this social stratum are frequently subjected to insufficient food, substandard housing, high levels of violence, and poor mental health, all of which may encourage them to use illicit drugs and engage in dangerous behaviors [48,49]. Those were 53% in a Mouritanian study with a significant relation to relapse [50].…”
Section: Residencymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a strong parent-adolescent relationship has been shown to reduce substance use in adolescents [ 24 ]. In contrast, lack of family support resulted in higher relapse among people with SUDs [ 25 ]. However, it is also vital that families must be educated about the difference between support and control, as control could be counterproductive.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that parental problems lead to a reduction in caregiving to the children, which make them more susceptible to peer pressure. Other studies have shown peer pressure is associated with initial substance abuse use as well as substance addiction (Lueck et al, 2020;Meister et al, 2020;Ramsewak et al, 2020;Randhawa et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 97%